Economic Value Added (Eva) Sebagai Pengukuran Kinerja Keuangan pada Industri Telekomunikasi Suatu Analisis Empirik - Trinik Susmonowati (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2018)
The company's performance has always been measured based on financial ratios for a certain period. Measurement based on financial ratios is very dependent on the accounting treatment used in the preparation of corporate financial statements. The purpose of a company that is only oriented to the achievement of profits as big as when it is no longer relevant today. Therefore the responsibility of the company not only to the shareholders, but to all stakeholders. Performance appraisal of a company is very important that the assessment process must be in line with the effectiveness and efficiency in achieving competitive advantage in the business world. Since the last ten years has developed a new approach in assessing the financial performance of companies known as Economic Value Added (EVA). EVA model comes from the concept of capital cost (cost of capital), which is the risk faced by the company in making investments. The concept of Economic Value Added (EVA) as an alternative to performance measurement based on the value (EVA) is an approach in assessing the performance of the company by paying fair attention to the expectations of funders or investors. EVA is the profit left behind after deducting the capital cost (cost of capital) invested to generate the profit. Positive EVA values can be interpreted that the company's management has created value (creating value). Conversely, if the value of negative EVA means that there is no economic value added into the company. The goal to be achieved by the authors in this study is To determine the financial performance of Telecommunications Company in review of Economic Value Edded (EVA). And To know Which Telecommunication Company that provides better economic value.This research used qualitative analysis. The qualitative analysis method is used to interpret and analyze the result of EVA calculation, that is to measure the added value of the company by calculating all capital cost, either the capital contribution from the shareholder or from the loan, or the risk faced by the company in making the investment. To measure the company's performance required financial report data in the form of income statement and balance sheet, JCI, stock price and SBI rate data. Data Collection Procedure is the data of financial statements of companies from the telecommunications industry listed on the Indonesia Stock Exchange in the period 2005-2009, obtained from www.idx.co.id. Monthly monthly stock price index (IHSG) monthly from 2005-2009, interest rate of 12 month time deposit from 2005-2009 and stock price data used since 2005.The results show that only PT Telekomunikasi Indonesia Tbk alone can generate positive EVA, while PT Indosat Tbk and PT Bakrie Telecom Tbk generate negative EVA. Negative EVA values are caused by several factors, among others: because of the significant increase in fuel prices, followed by inflation and rising interest rates affecting people's purchasing power, rising capital costs and operational costs of both companies, the impact of the 2008 global financial crisis that affected on declining stock value and the impact of tariff war between telecommunication companies where telephone tariffs are lower and the decline in long distance call rates affects the telecommunication company's operating revenues.